Fraudulent transactions in an online world - CHUA, Eunice (Institutional Knowledge at Singapore Management University, 2021)
This article considers the new normal of online payment transactions and the guidelines applicable to the situation of a fraudulent transaction. How effective are they at protecting consumers? Are there concerns that need to be addressed?